Survey of Awareness and Attitude about Domestic Violence among Married Women in Fasa, During Coronavirus Quarantine, 1399 - Fatemeh Sadat Rahnama (Fasa University of Medical Sciences, 2020)
Background&  Objective: Today, domestic violence has increased significantly for various reasons and the quarantine period has increased this factor more than before. This study sought to investigate and determine the rate of domestic violence among married women in Fasa during the coronavirus disease, in 1399. Materials & Methods: This research is descriptive-analytical and cross-sectional research. The study population consisted of women referring to health centers in Fasa. The sample size was calculated using Cochran's formula and was estimated to be 267 people. The data collection tool was a questionnaire to assess the awareness and attitude and practice related to domestic violence against women. Data were analyzed using an independent t-test, one-way analysis of variance, and Pearson correlation coefficient. Results: The results showed that there was a significant relationship between awareness of spouse abuse and domestic violence (p<0.05) and this relationship was negative and inverse. There was also a significant relationship between attitudes toward spouse abuse and domestic violence (p <0.05) and this relationship was negative and inverse relationship. The difference between the mean scores of knowledge and attitude between groups of different ages, with different duration of the marriage and groups with different social and economic statuses was significant (p<0.05). However, the difference in knowledge scores between groups with different levels of education was not significant, but the difference in attitude scores between groups with different educations was significant. Conclusion: Increasing awareness and positive attitude towards spousal abuse reduces domestic violence and conversely, decreasing awareness and negative attitude towards spousal abuse increases domestic violence.